2017
DOI: 10.2174/1875399x01710010071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Four Weeks Detraining on Strength, Power, and Sensorimotor Ability of Adolescent Surfers

Abstract: Abstract:Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
0
15
0
3
Order By: Relevance
“…In the motor skills dimension, the lack of engagement in physical activity could have led to reductions in speed, technical accuracy, sensorimotor coordination, and movement flow (Tran et al, 2017;Jukic et al, 2020). There is evidence that only 2-4 weeks of training cessation can cause a significant and marked loss of performance in both active populations and elite athletes (see Sousa et al, 2019).…”
Section: Ce As a Career Change-eventmentioning
confidence: 99%
“…In the motor skills dimension, the lack of engagement in physical activity could have led to reductions in speed, technical accuracy, sensorimotor coordination, and movement flow (Tran et al, 2017;Jukic et al, 2020). There is evidence that only 2-4 weeks of training cessation can cause a significant and marked loss of performance in both active populations and elite athletes (see Sousa et al, 2019).…”
Section: Ce As a Career Change-eventmentioning
confidence: 99%
“…For Tran et al 30 , the effect of detraining for 4 weeks caused a considerable drop in the height of the vertical jump (-5.3%), in the peak vertical velocity (-3.7%) and in the isometric strength (-5.5%). In addition, the sensorimotor capacity decreased, indicating that the athletes took longer (61.4%) to reach stability in a landing task.…”
Section: Detraining Strength and Muscle Controlmentioning
confidence: 94%
“…Thus, attenuating loss of neuromuscular capability during this period is essential to ensure performance is not compromised when competition resumes. When interpreting the available resistance training research, it appears that strength may be partially or completely maintained in the short term (e.g., up to 3 weeks) [ 22 ] but will be compromised after 4 weeks (e.g., surfing athletes) [ 23 ] and begin to decay in team-sport athletes [ 24 ] and/or be substantially lost after 5 weeks without training in physically active males [ 25 ]. Tran et al [ 23 ] also noted a reduction in athletes’ sensorimotor ability which may be an important consideration where technical and/or skillful actions are required (e.g., complex WL movements).…”
Section: Training Cessation Effects On Muscle Strength Power Andmentioning
confidence: 99%
“…When interpreting the available resistance training research, it appears that strength may be partially or completely maintained in the short term (e.g., up to 3 weeks) [ 22 ] but will be compromised after 4 weeks (e.g., surfing athletes) [ 23 ] and begin to decay in team-sport athletes [ 24 ] and/or be substantially lost after 5 weeks without training in physically active males [ 25 ]. Tran et al [ 23 ] also noted a reduction in athletes’ sensorimotor ability which may be an important consideration where technical and/or skillful actions are required (e.g., complex WL movements). Further, Izquierdo et al [ 26 ] demonstrated reductions in maximal strength and power of 6% to 9% and 14% to 17% in the upper- and lower-limbs, respectively, following 4 weeks of a complete cessation of training in physically active men.…”
Section: Training Cessation Effects On Muscle Strength Power Andmentioning
confidence: 99%